Iatrogenic Errors during Root Canal Instrumentation Performed by Dental Students - Hendi, Seyedeh Sareh; Karkehabadi, Hamed; Eskandarloo, Amir (Iranian Endodontic Journal, 2019)
Introduction: The present study was set to investigate the training quality and its association with the quality of root canal therapy performed by fifth year dentistry students. Methods and Materials: A total number of 432 records of endodontic treatment performed by fifth year dentistry students were qualified to be further investigated. Radiographs were assessed by two independent endodontists. Apical transportation, apical perforation, gouging, ledge formation, and the quality of temporary restoration were error types investigated in the present study. Results: the prevalence of apical transportation, ledge formation, and apical perforation errors were significantly higher in molars in comparison with other types of teeth. The most prevalent type of error was the apical transportation, which was significantly higher in mandibular teeth. There was no significant differences among teeth in terms of other types of errors. Conclusion: The quality of training provided for dentistry students should be improved and endodontic curriculum should be modified. Keywords: Dental Students; Procedural Errors; Root Canal Therapy